Hemoglobin Differences by Race in Children With CKD - Atkinson, Meredith A. (2010)
BACKGROUND: There are known racial disparities in the prevalence of anemia in adults with chronic kidney disease (CKD), but these differences have not been well described in children. STUDY DESIGN: Cohort study, cross-sectional analysis. SETTING AND PARTICIPANTS: The Chronic Kidney Disease in Children (CKiD) Study is a multi-center prospective cohort study of children with mild-to-moderate CKD. This analysis included 429 children of African-American or white race. PREDICTOR: Race. OUTCOMES & MEASUREMENTS: This study examined the association of race with level of hemoglobin. Both multiple linear regression and generalized gamma modeling techniques were used to characterize the association between race and hemoglobin. RESULTS: 79% of the cohort was white, 21% African-American. Neither median hemoglobin levels nor frequency of ESA use differed by race. In multivariate analysis, lower levels of iohexol-measured glomerular filtration rate (mGFR), African-American race, and glomerular disease (vs. non-glomerular disease) as the underlying cause of CKD were independently associated with decreased hemoglobin levels; independent of GFR and CKD diagnosis, African-American children displayed average hemoglobin levels 0.6 g/dL (95% confidence interval −0.9, −0.2 g/dL) lower than those of white children. Generalized gamma modeling demonstrated that the differences in hemoglobin observed by race become more pronounced when moving from high to low in the overall hemoglobin distribution. LIMITATIONS: Cross-sectional analysis cannot establish causality, and data on iron stores were not available for all patients. CONCLUSIONS: African-American children compared to white children demonstrate lower hemoglobin values in CKD, independent of the underlying cause of CKD. These racial differences in hemoglobin appear to increase at the lower end of the hemoglobin distribution in this population.